2017
DOI: 10.1021/acs.joc.7b01261
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of CF3-Containing Vicinal Diamines

Abstract: The highly diastereoselective synthesis of CF-containing vicinal diamines by a convenient two-step procedure without the need to isolate the intermediate products is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…While β-fluorine elimination from ylide Ph 2 S + CH – CF 3 may readily occur, the Johnson–Corey–Chaykovsky reaction of aldehydes, imines, and α,β-unsaturated ketones with this ylide proceeded smoothly to afford the cyclization products with high diastereoselectivity when CsF was used as the base to suppress the β-fluorine elimination (Scheme a) . The cyclization of imines was applied to a one-pot synthesis of CF 3 -containing vicinal diamines (Scheme b) …”
Section: Sulfonium Saltsmentioning
confidence: 99%
See 1 more Smart Citation
“…While β-fluorine elimination from ylide Ph 2 S + CH – CF 3 may readily occur, the Johnson–Corey–Chaykovsky reaction of aldehydes, imines, and α,β-unsaturated ketones with this ylide proceeded smoothly to afford the cyclization products with high diastereoselectivity when CsF was used as the base to suppress the β-fluorine elimination (Scheme a) . The cyclization of imines was applied to a one-pot synthesis of CF 3 -containing vicinal diamines (Scheme b) …”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…54 cyclization of imines was applied to a one-pot synthesis of CF 3containing vicinal diamines (Scheme 19b). 55 The successful development of the fluorinated sulfonium ylide reagent (Ph 2 S + CH 2 CF 3 TfO − ) prompted us to further examine whether trifluoromethylcarbene (:CHCF 3 ) can be produced from ylide Ph 2 S + CH − CF 3 . It was found that the direct thermal S−CH bond cleavage to form :CHCF 3 cannot occur.…”
Section: Sulfonium Saltsmentioning
confidence: 99%
“…The aziridine ring was synthesized from N ‐tosyl‐ or N ‐mesyl‐imines, whereas N ‐Boc or N ‐Cbz‐imines proved to be unreactive under their experimental conditions. A few years later Xiao [64] and co‐workers applied the same process to N ‐tosyl vinyl‐imines leading to various vinyl aziridines (13 examples), which served as intermediates to the synthesis of CF 3 ‐containing vicinal diamines (Scheme 42, Eq. (b)).…”
Section: Fluoro‐ Monofluoromethyl‐ Difluoromethyl‐ and Trifluoromementioning
confidence: 99%
“…The synthesis of vicinal diamines is currently an interesting topic, as the molecules with the 1,2‐diamino structural unit not only are characteristic structural features of many nature products and drugs, but also play an important role in ligand design and organic chemistry . For instance, vicinal diamines are valuable synthetic intermediates that are extensively used in the preparation of nitrogen‐containing heterocyclic compounds (piperazines, imidazolines, imidazolidines, etc) as well as aliphatic amines (amino acids, amino alcohols, etc).…”
Section: Introductionmentioning
confidence: 99%